Dynamic attribute-based group signature with verifier-local revocation and backward unlinkability in the standard model. (1st January 2014) - Ali, Syed Taqi; Amberker, B.B.
Attribute-based group signature (ABGS) scheme is a group signature scheme where the group members possessing certain privileges (attributes) only are eligible for signing the document. In verifier-local revocation (VLR) schemes, only verifiers are involved in the revocation of a member, while signers are not. Backward unlinkability ensures that even after a member is revoked, signatures produced by the member before the revocation remain anonymous. There is an ABGS scheme with VLR feature in the literature but it neither supports backward unlinkability nor has attribute anonymity nor it is in standard model and moreover its signature length is not constant. We propose a VLR ABGS scheme with all these features in the standard model.